La comunidad LGBT+ en el Perú: los retos para incluirla y reconocer sus derechos en el siglo XXI - Gutiérrez Lúcar, Marcial Giovanni (2021)
This article will address the problems faced by the members of the LGBT+ community in the 21st century in Peru, from a social and legal perspective. This will allow the identification of the legislative changes that need to be regulated in order to achieve a society which is more inclusive and free from discrimination against minorities.